Reframing Human Enhancement: A Population Health Perspective - Cabrera, Laura Yenisa (Frontiers in Sociology, 2017)
The dominant understandings on human enhancement, such as those based on the therapy-enhancement distinction or transhumanist views, have been focused on high technological interventions directly changing biological and physical features of individuals. The individual-based orientation and reductionist approach that dominant views of human enhancement take have undermined the exploration of more inclusive ways to think about human enhancement. In this perspective, I argue that we need to expand our understanding of human enhancement and open a more serious discussion on the type of enhancement interventions that can foster practical improvements for populations. In doing so, lessons from a population health perspective can be incorporated. Under such a perspective, human enhancement focus shifts from changing the biological reality of individuals, to addressing environmental factors that undermine the optimal performance of individuals or that can foster wellness. Such a human enhancement perspective would be consistent with a population health approach, as it pursues more equitable and accessible interventions, on the path to addressing social inequality. Human enhancement does not need to be only about high-technological interventions for a selected group of individuals; rather it should be a continuous project aiming to include everyone and maximize the public benefit.